MRCP 1 : Basic Sciences, Neurology and Psychiatry - Ray, David W. ; Tobias, Edward ; O'Donaoghue, Donal J. and et.al (Knutsford PASTEST, 2005)
Part of "MRCP 1 Pocket Book" series, this book features questions and answers providing essential practice for the MRCP Part 1 exam.